Relationships between self-management strategies and physical activity and diet quality in women with polycystic ovary syndrome. Issue 1 (January 2022) - Pirotta, Stephanie; Lim, Siew S.; Grassi, Angela; Couch, Lynn Monahan; Jeanes, Yvonne M.; Joham, Anju J.; Teede, Helena; Moran, Lisa J.
Abstract: Objective: To determine the relationships of self-management strategies and physical activity (PA) and diet quality in women with PCOS. Methods: An online cross-sectional study involving women (n = 501), 18–45 years in the general Australian community with a self-reported PCOS diagnosis. The self-management and lifestyle behaviour questionnaires were completed between August 2017 and March 2018. Results: Implementation of PA related self-management strategies increased the odds of meeting PA recommendations [Odds ratio (OR): 2.929 (95%CI: 2.172, 3.951), p < 0.001] but had no association with body mass index (BMI) [OR: 0.–0.984 (95%CI: − 1.010, 0.959), p = 0.217] nor perception of self weight [OR: 1.382 (95% CI: 0.700, 2.725), p = 0.352]. Nutrition related self-management strategies were inversely associated with BMI [OR: − 0.115 (95%CI: − 7.159, − 0.980), p = 0.010] but had no association with diet quality [OR: 0.183 (95%CI: − 2.328, 2.800), p = 0.855], energy intake [OR: − 0.092 (95%CI: − 1204.443, 527.496) p = 0.438] or weight [OR: − 0.034 (95%CI: − 4.020, 1.930), p = 0.491]. Conclusions: PA self-management strategies were associated with meeting PA recommendations. Nutrition strategies were associated with lower BMI but not diet quality, energy intake or weight in women with PCOS. Practice implications: Other behaviour change determinants (e.g. education, skills and self-efficacy) should be considered when designing a PCOS lifestyle programme in conjunction with self-management strategies. Highlights: Use of nutrition self-management strategies help lower BMI in PCOS. Use of physical activity self-management strategies help increase exercise in PCOS. Diet quality does not improve with self-management strategies in PCOS. Diet quality is lowered due to low grains and fruit consumption in PCOS. Women with PCOS correctly perceived themselves as overweight or obese.